2015
DOI: 10.1136/bcr-2015-210198
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected headache: pituitary apoplexy in a pregnant woman on anticoagulation

Abstract: Pituitary apoplexy is a rare event in which the pituitary gland undergoes infarction or haemorrhage, most commonly in the setting of an underlying tumour. We report on apoplexy of an undiagnosed pituitary adenoma precipitated both by physiological enlargement of the pituitary in pregnancy and prophylactic anticoagulation from a history of deep vein thrombosis. The haemorrhage was managed conservatively without significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Analysis of cases treated conservatively showed that this is a viable and safe option in a patient without visual field defects. Overall, in 16 cases there was full recovery of endocrinological function and in 21 cases, various degree of insufficiency ranging from diabetes insipidus to panhypopituitarism and cranial nerve palsy being encountered (4,7,9,19,24,26,29,30,(35)(36)(37)(38)(39)(40)(41)(42)51). For 11 cases, long-time consequences were not noted.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cases treated conservatively showed that this is a viable and safe option in a patient without visual field defects. Overall, in 16 cases there was full recovery of endocrinological function and in 21 cases, various degree of insufficiency ranging from diabetes insipidus to panhypopituitarism and cranial nerve palsy being encountered (4,7,9,19,24,26,29,30,(35)(36)(37)(38)(39)(40)(41)(42)51). For 11 cases, long-time consequences were not noted.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with characteristic presentation and history of prolactinoma, the rapid identification of pituitary apoplexy with pituitary MRI or CT with contrast is key to determining appropriate treatment (107,108). Pituitary apoplexy can be precipitated by physiologic enlargement of the pituitary in pregnancy and prophylactic anticoagulation from history of deep vein thrombosis (109,110). In its most serious presentation, patients may have headache and visual changes accompanied by hypopituitarism.…”
Section: Evaluation Of Primary and Secondary Headachesmentioning
confidence: 99%
“…Pituitary apoplexy occurs when the pituitary gland develops an infarct or hemorrhage. This occurs most commonly when there is an underlying tumor or adenoma, which may be asymptomatic . Pituitary apoplexy is a rare cause of headache but it can have potentially serious outcomes if not found and treated adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Although movement and physical activity can exacerbate migraine pain, these factors were particularly notable in our patient and may, in retrospect, have suggested a secondary cause of headache. Headache in pituitary hemorrhage is felt to be multifactorial, due to increased volume within the sella region, meningeal irritation, stretching of the dura, and/or trigeminal nerve involvement inside the cavernous sinus . Pituitary apoplexy is a rare but important and potentially life‐threatening differential to consider in someone presenting with new onset severe headaches.…”
Section: Discussionmentioning
confidence: 99%